Analytical Possibilities of Rutherford Backscattering Spectrometry and Elastic Recoil Detection Analysis Methods - Phu, Vu Duc; Khiem, Le Hong; Kobzev, A. P.; Kulik, M. (Communications in Physics, 2016)
This paper presents the results of an experimental study of three samples containing various elements in the near-surface layers. The depth profiles of all the elements of different atomic masses from hydrogen to silver were investigated by Rutherford Backscattering Spectrometry (RBS) and Elastic Recoil Detection Analysis (ERDA). The experiments were performed by using the low-energy (about 2 MeV) 4He+ ion beams. The obtained results demonstrate the possibility of the RBS and ERDA methods in the investigation of depth profiles of any mass element with an atomic concentration of about 0.01 at.% and a depth resolution close to 10 nm.